Endometrial thickness significantly affects clinical pregnancy and live birth rates in frozen-thawed embryo transfer cycles. (2nd July 2016) - Bu, Zhiqin; Wang, Keyan; Dai, Wei; Sun, Yingpu
Abstract: In order to explore the relationship between endometrial thickness on the day of embryo transfer and pregnancy outcomes in frozen-thawed embryo transfer (FET) cycles, we retrospectively analyzed data from 2997 patients undergoing their first FET cycles from January 2010 to December 2012. All patients were divided into three groups (Group A, ≤8 mm; Group B, 9–13 mm; Group C, ≥14 mm) according to the endometrial thickness on embryo transfer day. Compared with patients in the other two groups, patients with thin endometrial thickness in Group A had significantly lower clinical pregnancy rate (33.4%, 41.3% and 45.4%, p < 0.01) and live birth rate (23.8%, 32.2% and 34.0%, p < 0.01). After adjusting for age, body mass index (BMI), baseline follicle stimulating hormone (FSH) FET protocol and number of embryos transferred, the associations between medium endometrial thickness (Group B) and clinical pregnancy rate [adjusted odds ratio (aOR): 1.39; 95% confidence interval (CI): 1.10–1.77, p < 0.01] and live birth rate (aOR: 1.50; 95% CI: 1.16–1.95, p < 0.01) were significant. We conclude that for patients undergoing FET, endometrial thickness on the embryo transfer day significantly affects IVF outcomes in cleavage embryo transfer cycles independent of other factors.